2011
DOI: 10.1007/s12011-011-9072-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resistance Exercise on Iron Status in Moderately Iron-Deficient Rats

Abstract: Resistance exercise increases heme synthesis in the bone marrow, but it does not improve the hemoglobin status in severe iron-deficient rats on a diet containing less than 5 mg iron/kg. The current study investigated whether resistance exercise could mitigate hemoglobin status via increasing heme synthesis in moderately iron-deficient rats. Male 4-week-old Sprague-Dawley rats were fed an iron-deficient diet containing 12 mg iron/kg for 3 weeks. The rats were divided into two groups: a sedentary (S) group (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Second, just as the meats and vegetables eating pattern score increased from Q1 to Q4, the proportion of those who "have exercise habits" increased among the older elderly, though not significantly among the younger elderly. According to a previous study, resistance exercise improved hemoglobin status by increasing heme synthesis in the bone marrow in moderately iron-deficient rats (36), which could decrease the risk of anemia among the older elderly. A previous study reported that blood hemoglobin level was associated with physical performance in the community-dwelling elderly, similar to our result (37).…”
Section: Discussionmentioning
confidence: 96%
“…Second, just as the meats and vegetables eating pattern score increased from Q1 to Q4, the proportion of those who "have exercise habits" increased among the older elderly, though not significantly among the younger elderly. According to a previous study, resistance exercise improved hemoglobin status by increasing heme synthesis in the bone marrow in moderately iron-deficient rats (36), which could decrease the risk of anemia among the older elderly. A previous study reported that blood hemoglobin level was associated with physical performance in the community-dwelling elderly, similar to our result (37).…”
Section: Discussionmentioning
confidence: 96%
“…The rats were randomly divided into three groups: a group sacrificed at the start date (week 0, n=7), a group that remained sedentary for 6 weeks (S, n=7), or a group that performed exercise for 6 weeks (E, n=7). The rats in the E group performed a climbing exercise from 1700 to 1800 hours, with 5 min of rest between the exercise sessions each day during the 6-week study period, as reported previously [7,19]. The body weight of the rats and the food intake were measured every day throughout the study.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…The bone marrow δ-aminolevulinic acid dehydratase (ALAD) activity, the key enzyme involved in hemoglobin synthesis, is increased after resistance exercise and decreases with time [5]. In addition, the bone marrow ALAD activity is maintained at a high level by routine resistance exercise training, compared with that in sedentary rats [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it led to an increased concentration of growth hormone, which was speculated to be responsible for improved hematopoiesis observed after an exercise program in patients with chronic disease [82]. Matsuo and colleagues [83,84,85,86,87,88,89] conducted animal studies and reported that long-term resistance exercise is more effective than aerobic exercise in improving iron status and blood Hb in moderately and severely iron-deficient rats by increasing heme synthesis in the bone marrow. They suggested that resistance exercise may be a useful preventive therapy for iron deficiency anemia.…”
Section: Could Exercise Training Improve Anemia?mentioning
confidence: 99%